Peningkatan Keterampilan ICT melalui Pelatihan Pembuatan Kuis Online - Yuniawatika Yuniawatika; Ibrahim Sani Ali Manggala (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the characteristics of 21st century teachers is having ICT skills that can be used in the learning process. Therefore, in this community service, the PKM team held training on making online quizzes for teachers in the UM Labschool in Blitar City. The purpose of this service is that teachers have insight and skills about developing test instruments, and are skilled at using online applications, namely Google Form, Quizizz, and Plickers that can support the learning process. The method of implementing this service activity is carried out by lectures, demonstrations and practices, giving assignments, discussions, and presentations. 17 paticipans have attended the training with discipline and order. The results of community service showed that all participants were able to develop good test instruments and were accompanied by the selected online quiz link. It showed that there was an increase in participants' understanding before and after participating in this training activity. This activity makes a meaningful contribution to partners in the midst of the Covid 19 pandemic which requires distance learning.